Automation with Basic Microbiology Techniques: The Synergy Vibrates at a Higher Octave for Clinical Anaerobic Bacteriology and Antimicrobial Stewardship - Butta, Hena; Snigdha, Ghanta Naga Sai; Mendiratta, Leena; Sardana, Raman; Prasad, Arun; Goel, Neerav; Dash, Kiranbala (Annals of Pathology and Laboratory Medicine, 2025)
Background: Anaerobic bacteria are the most common normal flora that colonizes the skin and lines the mucosal surfaces of our body. Anaerobic infections are most often overlooked, and failure to provide specific antimicrobial coverage to these organisms may result in therapeutic failure. The aims of our study were to look for the Microbiology profile, antimicrobial susceptibility, and clinical correlates of various anaerobic bacteria isolated from various clinical specimens of patients using automated techniques, i.e., Anoxomat and MALDI-TOF MS/Vitek-2. Methods: All the specimens received for anaerobic culture were processed as per standard guidelines. Direct microscopic examination of each of the specimens was also done. Identification of anaerobic bacteria was done by MALDI-TOF Vitek MS and/or Vitek-2. Antimicrobial susceptibility testing was performed using the E-test method, and interpretation was done as per CLSI guidelines. Results: A total of 910 specimens were received for anaerobic culture during the study period. Out of 910 specimens, a total of 71 bacteria were isolated anaerobically. Out of these 71 isolates, 54 were obligate anaerobes and 17 were facultative anaerobes. Out of 54 obligate anaerobes, Bacteroides sp. was isolated maximally (27.7%) followed by Prevotella sp. (24.0%). The various clinical specimens from which these anaerobes were recovered mainly included abdominal pus, perianal abscess, High vaginal swab, Urethral pus, and Breast abscess. Metronidazole resistance in Bacteroides sp. was found to be 30.7%, whereas in Prevotella sp. it was comparatively low (25%). Facultative anaerobes like various species of Streptococcus from deep-seated abscesses like Brain abscess were isolated anaerobically only. Conclusion: Accurate and rapid detection of anaerobes due to automated methods synergizes with basic microbiological techniques, which leads to early institution of targeted therapy and thus helps in antimicrobial stewardship. Initial isolation of facultative anaerobes under anaerobic conditions only is also an interesting area of research.